Antimicrobial susceptibility, serotypes and genotypes of Pasteurella multocida isolates associated with swine pneumonia in Taiwan. (21st September 2017) - Yeh, Jih‐Ching; Lo, Dan‐Yuan; Chang, Shao‐Kuang; Chou, Chi‐Chung; Kuo, Hung‐Chih
Abstract : Pasteurella multocida (PM) can cause progressive atrophic rhinitis and suppurative bronchopneumonia in pigs. The present study performed antimicrobial susceptibility testing and serotype and genotype identification on the 62 PM strains isolated from the lungs of diseased pigs with respiratory symptoms. Antimicrobial susceptibility testing examined 13 antimicrobial agents (amoxicillin, cefazolin, doxycycline, flumequine, enrofloxacin, florfenicol, kanamycin, lincomycin, Linco‐Spectin (lincomycin and spectinomycin), erythromycin, tylosin, tilmicosin and tiamulin). Antimicrobial resistance ratios were over 40% in all of the antimicrobial agents except for cefazolin. The highest levels of resistance (100%) were found for kanamycin, erythromycin and tylosin. The majority of isolated strains was serotype D:L6 (n=35) followed by A:L3 (n=17). Comparison of the antimicrobial resistance levels between the two serotypes showed that the antimicrobial resistance rates were higher in D:L6 than in A:L3 for all the tested antimicrobials except for tylosin and tilmicosin. For PM with erm (B), erm (T) or erm (42), the results showed no significant difference compared with non‐resistance gene strains in phenotype. Pulsed‐field gel electrophoresis genotyping using Apa I restriction digestion of the genomic DNA demonstrated that there were 17 distinct clusters with a similarity of 85% or more, and the genotyping result was similar to that of serotyping. The results of the present study demonstrated that the PM isolated from diseased pigs in Taiwan was resistant to multiple antimicrobials, and the distribution of antimicrobial resistance was associated with pulsotype and serotype.